An international survey of SEEG cortical stimulation practices - Emily Cockle; Genevieve Rayner; Charles Malpas; Rubina Alpitsis; Sylvain Rheims; Terence J O'Brien; Andrew Neal (Epilepsia Open, 2023)
Abstract Objective Cortical stimulation is an important component of stereoelectroencephalography (SEEG). Despite this, there is currently no standardized approach and significant heterogeneity in the literature regarding cortical stimulation practices. Via an international survey of SEEG clinicians, we sought to examine the spectrum of cortical stimulation practices to reveal areas of consensus and variability. Methods A 68‐item questionnaire was developed to understand cortical stimulation practices including neurostimulation parameters, interpretation of epileptogenicity, functional and cognitive assessment and subsequent surgical decisions. Multiple recruitment pathways were pursued, with the questionnaire distributed directly to 183 clinicians. Results Responses were received from 56 clinicians across 17 countries with experience ranging from 2 to 60 years (M = 10.73, SD = 9.44). Neurostimulation parameters varied considerably, with maximum current ranging from 3 to 10 mA (M = 5.33, SD = 2.29) for 1 Hz and from 2 to 15 mA (M = 6.54, SD = 3.68) for 50 Hz stimulation. Charge density ranged from 8 to 200 μC/cm2, with up to 43% of responders utilizing charge densities higher than recommended upper safety limits, i.e. 55 μC/cm2. North American responders reported statistically significant higher maximum current (P < 0.001) for 1 Hz stimulation and lower pulse width for 1 and 50 Hz stimulation (P = 0.008, P < 0.001, respectively) compared to European responders. All clinicians evaluated language, speech, and motor function during cortical stimulation; in contrast, 42% assessed visuospatial or visual function, 29% memory, and 13% executive function. Striking differences were reported in approaches to assessment, classification of positive sites, and surgical decisions guided by cortical stimulation. Patterns of consistency were observed for interpretation of the localizing capacity of stimulated electroclinical seizures and auras, with habitual electroclinical seizures induced by 1 Hz stimulation considered the most localizing. Significance SEEG cortical stimulation practices differed vastly across clinicians internationally, highlighting the need for consensus‐based clinical guidelines. In particular, an internationally standardized approach to assessment, classification, and functional prognostication will provide a common clinical and research framework for optimizing outcomes for people with drug‐resistant epilepsy.